(untitled) (Aristonothos. Rivista di Studi sul Mediterraneo Antico, 2010)
The Palikoì are twin heroes revered in Sicily, in the Margi valley. This worship played a crucial role in the acknowledgement by the Sicilian communities of their own identity. In fact, not only it is archaic, but, on the ground of the architectural and ritual characteristics, it is also possible to follow its evolution, inspired to Greek models, both in archaeological finds and in literary sources. The cult was started in a cave in front of a small lake, a location that witnessed a monumental evolution in the V century b.C. with an hestiaterion; the continuity in site patronage is proven at least until the III century a.D. (excavations by P. Pelegatti and, subsequently, by B. McConnel and L. Maniscalco). Literary sources (Diodorus of Sicily, first of all) attest a locus inferus, whose waters are extremely important as guarantee in pledges and as solver of disputes among contenders of different social levels (e.g. slaves vs. masters, Greeks vs. Sicilians).